2015
DOI: 10.1039/c5dt03373j
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of terminal modification of [Ru(phen)2dppz]2+on the luminescence properties: a theoretical study

Abstract: [Ru(phen)2dppz](2+) and other closely related ruthenium(II) complexes containing π-extended ligands were found to be non or weakly emissive in water, while exhibiting significant luminescence intensity growth when bound to DNA, however, a satisfactory interpretation has not been provided on this "light switch" mechanism. In the present study, we investigated the vertical transitions and triplet excited states of [Ru(phen)2dppz](2+) (1), [Ru(phen)2dppzi](2+) (2) and [Ru(phen)2dppz-idzo](2+) (3) in the gas phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A decrease in electron density on the Ru metal centre was also observed in both cases, which indicated that the triplet lowest excited states in both solvents have substantial metal-to-ligand charge-transfer character, with additional small contributions from a purely dppz ligand-centred transition. 19 22 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in electron density on the Ru metal centre was also observed in both cases, which indicated that the triplet lowest excited states in both solvents have substantial metal-to-ligand charge-transfer character, with additional small contributions from a purely dppz ligand-centred transition. 19 22 …”
Section: Resultsmentioning
confidence: 99%
“… 5 , 31 While these studies clearly point to the presence of two distinct excited states, there has been some disagreement about the nature of these states in the literature, especially from computational studies. 19 22 …”
Section: Introductionmentioning
confidence: 99%
“…3). 62,63 A similar calculation considering 40 excitations (with triplet state optimized) was used as the basis for the selfconsistent two-component spin-orbit coupling TDDFT (SOC-TDDFT) 64 within the ZORA Hamiltonian, where 6 spin-mixed excitations were calculated using the SR-TDDFT results as input. 27,65,66 Since the T 1 state is the lowest in the triplet manifold, the T 1 geometry can be optimized like a regular ground state.…”
Section: Methodsmentioning
confidence: 99%
“…3). 62,63 Usually, the triplet state is lower in symmetry than the ground state; thus, it is not recommended to consider symmetry restrictions. In this part of the work, we are interested in electronic transitions between the visible and ultraviolet regions.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for Ru­(II) dppz complexes, the luminescence is switched off in protic solvents . Several modifications on the dppz ligand were introduced in the past three decades, and their effect on the photophysical properties were investigated thoroughly. Importantly, related oligopyridophenazines strongly related to the dppz core play an important role in artificial photosynthesis and directional photoinduced electron-transfer reactions. , …”
Section: Introductionmentioning
confidence: 99%